Why and how vaccines work (2020)
Vaccines have substantially reduced the burden of infectious diseases. An estimated 103 million cases of childhood diseases were prevented between 1924 and 2010 in the United States through vaccination (van Panhuis et al., 2013). In particular, the eradication of smallpox through vaccination in 1980 is one of the crown achievements of medicine. Until then, smallpox had afflicted humanity for at least 3,000 years, killing 300 million people in the twentieth century alone. Vaccines prevent diseases caused by a large number of viruses and bacteria, and those against parasites are under development. Vaccines are also one of the most effective investments in humanity. Every dollar spent on vaccines yields an estimated $44 in economic returns, by ensuring children grow up healthy and are able to reach their full potential (Ozawa et al., 2016).